Comparative study of the undergraduate community-based nursing curriculum in Shahid Beheshti university of medical sciences, school of nursing and linfield school of nursing - Arezoo Zeydani; Foroozan Atashzadeh-Shoorideh; Meimanat Hosseini; Sima Zohari-Anboohi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Revising UCBNC using successful education systems in the world to guarantee the quality of the curriculum is necessary. This study aimed to compare the undergraduate community-based nursing curriculum at Shahid Beheshti University of Medical Sciences, School of Nursing, and Linfield School of Nursing. MATERIALS AND METHODS: The present comparative descriptive study was conducted using Beredy's four-step approach (description, interpretation, juxtaposition, and comparison) in 2022 and searched the required data using keywords. The fundamental elements of the community-based nursing curriculum were collected and analyzed from the website and internal and external databases. RESULTS: The findings of this study showed that there are main differences in the curriculum of the two schools. All dimensions of the Linfield School of Nursing curriculum are designed based on the community-based nursing education model focusing on communication, community, cultural diversity, health, social justice, stakeholder engagement, evidence-based practice, and responding to community needs. Still, the attention and emphasis on the mentioned items in Iran's curriculum are fragile. CONCLUSIONS: The nursing curriculum in Iran should be revised based on the community-based nursing education model, and according to the local conditions, background, and community needs so that can be achieved to the maximum productivity and efficiency of nurses using meet the community needs.